Potential Protective Effect of Atriplex halimus Extract toward the Doxorubicin - Induced Apoptotic Gene Expression, Genetic and Hepatic Toxicity in Mice - Shenouda M. Girgis (Journal of Global Pharma Technology, 2020)
Objective: The anthracycline doxorubicin (DOX) is widely used in chemotherapy as an anticancer drug due to its efficacy in fighting a wide range of cancers such as carcinomas, sarcomas and hematological cancers. However, it can induce injury to non-targeted organs after cancer treatment. Thus, exploration of effective drug targets or active lead compounds against DOX-induced organ damage is necessary. Method: In this study the protective effect of Atriplex halimus (Ah) extract towards DOX-induced genetic and hepatic toxicity and apoptosis in male mice was investigated. Animals were divided into 7 groups (10 animals each): 1- Control group treated with physiological saline. 2- Animals treated with DMSO. 3- Low dose of Ah (0.5 mg/kg bw) extracts. 4-high dose of Ah (5mg/kg bw) extracts. 5- Animals were injected i.p with DOX. 6- DOX + low dose of Ah (0.5 mg/kg bw) extracts for 1 week. 7- DOX + high dose of Ah extracts for 1 month. Results: DOX treatment induced a significant increase in the chromosomal aberrations either in the bone marrow or in the spermatocyte cells, increase the DNA fragmentation, malondialdehyde (MDA) level and the expression of apoptosis-related genes, Bax and caspase 3 genes. However, the treatment with Ah declined these negative effects. Conclusion: The findings demonstrated that Ah extract had protected the mice against the negative effects of DOX-induced genetic, hepatic toxicity and apoptosis and could be used as natural antioxidant product for scavenging the reactive oxygen species and to attenuate DOX-induced genetic and hepatic toxicity. Keywords: Doxorubicin (DOX), Atriplex halimus (Ah), Apoptosis, Gene expression, Genotoxicity, Hepatic, mice.